A real-time, quantitative PCR method using hydrolysis probes for the monitoring of Plasmodium falciparum load in experimentally infected human volunteers - Rockett, Rebecca J; Tozer, Sarah J; Peatey, Chris; Bialasiewicz, Seweryn; Whiley, David M; Nissen, Michael D; Trenholme, Katharine; Mc Carthy, James S; Sloots, Theo P (Malaria journal, 2011)
The accurate quantification of Plasmodium falciparum parasite numbers by PCR is an important tool for monitoring growth kinetics in subjects infected and subsequently treated with anti-malarial agents. A real-time quantitative PCR (rt-qPCR) method using primers and a hydrolysis probe that targets the 18S rRNA gene was adapted and optimized to estimate parasite load in blood samples. Samples included laboratory prepared blood samples of varying parasite concentrations (6.4 × 10(5) to 6.4 parasites per 500 μl of packed red blood cells (500pRBC)) and blood samples collected from an experimentally infected human subject collected at 19 time points over 10 days. Sample preparation and extraction, detection chemistry, assay reproducibility, and limit of detection were compared to a previously published SYBR Green rt-qPCR used in a malaria vaccine clinical trial. Both the rt-qPCR hydrolysis probe assay and SYBR Green rt-qPCR provided a limit of detection of 6.4 × 10(1) parasites per 500pRBC. However non-specific amplification in the SYBR Green rt-qPCR assay led to either inaccurate estimation of parasite load at levels below 6.4 × 10(2) parasites per 500pRBC and to false-positive detection of parasites in negative samples. The rt-qPCR hydrolysis probe assay was specific and provided reliable quantification of parasitaemia down to 6.4 × 10(1) parasites per 500pRBC. Notably, 12 of the 19 consecutive samples collected from the experimentally infected subject were at or below 6.4 × 10(2) copies per 500pRBC. These results show that the hydrolysis probe rt-qPCR assay is superior to the SYBR Green rt-qPCR for the quantification of P. falciparum in human blood samples. The hydrolysis probe rt-qPCR is now in use in the Queensland paediatric infectious diseases laboratory (QPID) to monitor parasitaemia in experimentally-infected clinical trial subjects.